Decolorization and mineralization of C.I. direct red 28 azo dye by ozonation. Issue 9 (19th February 2016) - Venkatesh, Smita; Quaff, A.R.; Pandey, N.D.; Venkatesh, K.
Abstract: This study evaluated the efficiency of ozonation for removal of color and chemical oxygen demand (COD) of Congo red, as an anionic dye was selected due to the complex chemical structure with di-azo aromatic group and extended application in the textile industry. The effect of ozonation time on the rate of COD removal, mineralization and rate of decolorization were studied and the result was analyzed in terms of COD and color removal efficiency. Intermediate and final by-products formed during ozonation were identified by ion chromatography (IC). Dye decomposition rate was observed by UV–vis spectroscopy. The removal of COD and color of Congo red by ozonation was performed in a batch reactor with constant ozone flow rate and concentration of 5 g/hr and 55.5 mg/L, respectively. Dye concentration was 1, 500 mg/L. Decolorization and degradation of dye sample were carried out with a certain time interval and analyzed immediately. The COD and color removal efficiencies increase at specified time of ozonation. After 15 min of ozonation time, the COD of Congo red was increased. Results with Congo red synthetic dye solution showed the maximum COD reduction of 67%, obtained after 10 min of ozonation. The reduction of COD showed partial degradation of this dye. Ninety percentage of color removal was achieved after 25 min of ozonation time. Dyes are completely destroyed with the formation of final product chloride, fluoride, sulfate, nitrate, and oxalate ions analyzed by ion chromatography. During ozonation process, rapid decrease of pH gave evidence for production of acidic by-products. The effect of buffered solutions (phosphate buffer) on the dye solutions was further investigated in this study. Ozonation also resulted in increase of electrical conductivity of the dye solution.